O8.1. ASSOCIATION BETWEEN GENETIC AND ENVIRONMENTAL RISK FOR SCHIZOPHRENIA DURING UPBRINGING: FINDINGS FROM A LONGITUDINAL COHORT STUDY. (18th May 2020) - Newbury, Joanne; Arseneault, Louise; Caspi, Avshalom; Moffitt, Terrie; Odgers, Candice; Belsky, Dan; Matthews, Tim; Fisher, Helen
Abstract: Background: Associations of environmental exposures such as urban upbringing, deprivation and crime victimization with psychosis are well-established. An enduring question, however, is whether associations reflect a causal process. Emerging evidence using polygenic risk scores (PRS) suggests reverse causation, with adults at higher genetic risk for schizophrenia being more likely to live in crowded and deprived areas. This process could occur due to the downward mobility of individuals at higher genetic risk for schizophrenia into more disadvantaged environments. However, the handful of studies on this topic to date have typically focused on environmental conditions during adulthood and have typically examined only macro-level environmental features (e.g., urbanicity). Methods: We examined associations between two measures of genetic risk (PRS for schizophrenia and family psychiatric history) with multiple features of children's family-, neighborhood-, and wider- environments during upbringing. Data were from the Environmental Risk (E-Risk) Longitudinal Twin Study, a nationally-representative cohort of 2, 232 British twins born in 1994–1995 and followed to age 18 (with 93% retention). Environmental risk factors were measured from early childhood to late adolescence, and included urbanicity, air pollution, neighborhood deprivation, neighborhood crime, neighborhood disorder, social cohesion, family poverty, residential mobility, and crime victimization. At age 18, participants were privately interviewed about psychotic experiences (e.g., hallucinations and delusions) occurring since age 12. Results: Children with higher schizophrenia PRS and a greater family psychiatric history were exposed to a wide range of riskier environments during upbringing. For schizophrenia PRS, associations were significant at p<0.05 for neighborhood crime (OR=1.16, 95% CI=1.04–1.29), neighborhood disorder (OR=1.16, 95% CI=1.04–1.30), family poverty (OR=1.12, 95% CI=1.10–1.25) and residential mobility (OR=1.24, 95% CI=1.10–1.40). In contrast, for family psychiatric history, associations were significant at p<0.05 for family poverty (OR=1.26, 95% CI=1.11–1.42), residential mobility (OR=1.32, 95% CI=1.17–1.50), and crime victimization (OR=1.24, 95% CI=1.12–1.38). However, associations between environmental risks and adolescent psychotic experiences were essentially unchanged after controlling for schizophrenia PRS and family psychiatric history. Discussion: Consistent with a degree of reverse causation, we found that children with higher genetic risk for schizophrenia also experienced riskier environments during upbringing. In particular, children at higher genetic risk were more likely to grow up in dangerous neighborhoods, poorer families, and move houses more frequently across childhood. However, genetic risk for schizophrenia (using polygenic risk scores and family psychiatric history) does not appear to confound associations of environmental risks with early expressions of psychosis. Nevertheless, future research into environmental conditions and psychosis should acknowledge and ideally examine the possibility of reverse-causation due to the downward mobility of individuals at higher genetic risk for schizophrenia into riskier environments.